Determination of matrix composition for diamond cutting tools according to the hardness and abrasivity properties of rocks to be cut - GÜNDÜZ, OĞUZHAN (ELSEVIER SCI LTD, 2021)
Diamond is a suitable material for cutting applications of rocks due to its outstanding properties like high hardness, great toughness, high thermal conductivity, low friction and high wear resistance. It is therefore used as the reinforcing agent in diamond cutting tools in which diamond is dispersed in a metal matrix. As rocks may exhibit different abrasiveness due to their inherent properties in the cutting operations, composition of the metal matrix should be carefully selected based on hardness and abrasivity of rocks. One of the main criteria in this selection is to ensure that diamond and metal matrix wear are as close as possible to each other, and thus to improve the service performance of the tool during cutting. The objective of this study is therefore to enhance the cutting performance of diamond tools by determining a suitable matrix composition according to hardness and abrasiveness of the rocks. For this purpose, two metal matrix compositions of Co- and Fe-based were selected and their microstructures, mechanical properties and wear properties were comparatively investigated. Micro structural, physical and mechanical characterizations were performed by SEM-EDS, XRD, density measurement, hardness measurement, compression tests and wear tests. The cutting performance of the samples was also evaluated by on-site field tests. Results showed that the mechanical properties of different matrix composition, hardness and wear resistance of Co-based matrixes are higher than those of Fe-based matrixes. On-site field tests revealed that Fe-based matrix is more suitable for cutting marble, while Co-based matrix is more suitable for cutting granite.
Keywords: Diamond; Diamond cutting tools (DCT); Metal matrix; Rock mechanics; Rock cutting process; Type of rocks; Mining science; WEAR; FE; ALLOYS; MARBLE